2013
DOI: 10.1186/1742-2094-10-122
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative cerebrospinal fluid cytokine levels and the risk of postoperative delirium in elderly hip fracture patients

Abstract: BackgroundAging and neurodegenerative disease predispose to delirium and are both associated with increased activity of the innate immune system resulting in an imbalance between pro- and anti-inflammatory mediators in the brain. We examined whether hip fracture patients who develop postoperative delirium have altered levels of inflammatory mediators in cerebrospinal fluid (CSF) prior to surgery.MethodsPatients were 75 years and older and admitted for surgical repair of an acute hip fracture. CSF samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 70 publications
3
61
1
1
Order By: Relevance
“…Postoperative CRP is a sensitive marker for detecting postoperative complications, especially delirium, in elderly patients undergoing hip fracture surgery. [ 20 2125 ] In agreement with previous studies, our results showed that patients with postoperative delirium had higher pre- and postoperative CRP levels than did those without. Delirium per se is associated with an increased risk of death in elderly patients with hip fractures.…”
Section: Discussionsupporting
confidence: 92%
“…Postoperative CRP is a sensitive marker for detecting postoperative complications, especially delirium, in elderly patients undergoing hip fracture surgery. [ 20 2125 ] In agreement with previous studies, our results showed that patients with postoperative delirium had higher pre- and postoperative CRP levels than did those without. Delirium per se is associated with an increased risk of death in elderly patients with hip fractures.…”
Section: Discussionsupporting
confidence: 92%
“…These findings suggest that the underlying mechanisms governing the development of delirium in patients with inflammation may differ from those without inflammation. 68 Others have found cytokines such as insulin-like growth factor (IGF)-1, IL-1β and IL-1 receptor antagonist (RA) to be associated with delirium, 69-71 and high levels of interferon (IFN-γ) with low levels of IGF-1 were associated with delirium severity. 72 S100B, a marker of astrocyte damage, has been shown to be elevated in delirium, both in plasma and in CSF.…”
Section: Evidence Linking Delirium and Dementiamentioning
confidence: 99%
“…Delayed or impaired sleep can cause disruption of the circadian rhythm, which has been associated with delirium . Rodent studies demonstrate that sleep disruption impairs innate immune defense, which may lead to the inflammatory dysregulation associated with postoperative delirium . Sleep, then, may contribute over the long term to the integrity of brain homeostatic mechanisms that enable resilience in the face of stressors such as surgery.…”
Section: Discussionmentioning
confidence: 99%